Analysis of Parent Cooperation in Early Childhood Education Institutions - Vevi Sunarti; Jamaris Jamna; Sufyarma Marsidin (Universitas Negeri Padang, 2021)
Children's education cannot be separated from the large contribution of parents, who realize it or not will have a considerable influence on the success of an education. Therefore, in any situation, the role of parents cannot be ignored. One of the things we can observe is the need for parental cooperation in the implementation of existing education in an educational institution, we call it an early childhood education institution. Early childhood education cannot be separated from the cooperation of parents, the low cooperation of parents with early childhood education institutions will affect the success of the program itself. In this study the researchers tried to analyze the things that caused the low work of parents in early childhood education institutions, questionnaires were distributed to 21 who had children who were in early childhood education institutions and distributed randomly. With the results of good job research in terms of orientation to tasks that are considered quite good, (2) Orientation to the process which is considered quite good (3) Orientation to the assessment is quite low. The conclusions we can draw from this research are the need for an approach given to parents, so that parents want to be involved and cooperate in early childhood education institutions.